Tailoring the optical and magnetic properties of ZnS nanoparticles via 3d and 4f elements co-doping. (January 2021) - Poornaprakash, B.; Chalapathi, U.; Kumar, Mirgender; Vattikuti, S.V. Prabhakar; Rajitha, Beerelli; Poojitha, P.T.; Park, Si-Hyun
Abstract: Impurity free cobalt 3 d and erbium 4 f co-doped ZnS nanoparticles (NPs) were synthesized using a chemical reflux technique. The as-synthesized NPs exhibited high crystallinity and a narrow particle-size distribution. X-ray diffraction and optical analysis showed that cobalt (II) and erbium (III) ions substituted the zinc (II) ions in tetrahedral sites. The tunable bandgap for ZnS NPs was attained through mono- and co-doping. The cobalt and erbium co-doped NPs displayed a robust magnetization with an enhanced coercivity at room temperature compared with the cobalt-doped ZnS NPs; this was due to the exchange interaction between the cobalt (II) electrons as well as the localized carriers incited through the erbium (III) co-doping. The sense captured with the regulating bandgap and ferromagnetic property in a single substance opens a new platform for advanced applications in optoelectronics and spintronic devices.